“Hanging Out,” Creativity, and the Right to the City: Urban Public Space in Russia before and after the Protest Wave of 2011–2012 - Zhelnina, Anna (Stasis, 2014)
The article discusses issues of urban public space in Russian cities within the context of the 2011–2012 anti-electoral fraud protests. The role of urban public space and its contestation has been central to the debate around the worldwide Occupy movement, but it is important to contextualize the protest movements in terms of national and local developments in the uses of public space. Therefore, the article focuses on post-socialist transformations of public space in the Russian cities of Saint Petersburg and Moscow. Representations and perceptions of public space are examined via media analysis (including mass